Seroepidemiological Screening For Toxoplasmosis Within Unmarried Women In Basrah Province - Ghalib Noori AL-Mousawi; Wafaa Sadoon Shani (University of Thi-Qar Journal of Science, 2019)
Current study included Seroepidemiological Screening of 450 sera from unmarriedwomen, within age ranged between (15 – 45) year by using IgG and IgM Enzyme LinkedImmunosorbent Assay (ELISA) test. Sera collected from areas of Basrah province and fromdifferent classes ( students , officials and housewives ) , and according to the primary health caredepartment program the province was divided into eight sections .Results documented that the prevalence rate of the disease in unmarred women in thewhole province was 58% while the prevalence rates of sections was as follows : Sec I 63.2% , SecII 51.8% , Al – Midayna 75% , AI – Qurna 64% , Al – Hartha 70% , Shatt – al – Arab 55% , Abu– al – Khaseeb 67.5% and Al – Zubair 36.3% . The higher rate recorded in Al – Midayna andlower rate in Al – Zubair .According to age group there is a significant difference ( P<0.025 ) and the results showedthat (15 - 19) year with the rate of infection 64.54% , (30-34) year with rate 60.7% , (35-39) yearwith rate 60%, while the results upon sociodemographic data recorded that the housewives (all ofthem with low level of learning) represents rate 62.4% in comparison with students 45% andofficials 44% , with a significant differences ( P < 0.05 ) .